2012
DOI: 10.1080/14681811.2011.601172
|View full text |Cite
|
Sign up to set email alerts
|

Education about sexuality in the elderly by healthcare professionals: a survey from the Southern Hemisphere

Abstract: Education about sexuality is one method of reducing common negative stereotypes about this aspect of the life of older people. Knowledge and attitudes toward sexuality are therefore particularly important in those who educate healthcare professionals. We surveyed schools of medicine, nursing, occupational therapy, physiotherapy, psychology, and social work in Australia, New Zealand, and South Africa using White\u27s Aging Sexuality Knowledge and Attitudes Scale. A total of 364 usable surveys were returned, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…Sexuality education is a method to reduce common negative stereotypes about this aspect of life [6] and it is not yet widespread in medical practice to investigate and treat sexual dysfunction. A rational approach to the problem should involve in-depth discussion and investigation of the root causes.…”
Section: Introductionmentioning
confidence: 99%
“…Sexuality education is a method to reduce common negative stereotypes about this aspect of life [6] and it is not yet widespread in medical practice to investigate and treat sexual dysfunction. A rational approach to the problem should involve in-depth discussion and investigation of the root causes.…”
Section: Introductionmentioning
confidence: 99%
“…In multiple regression analysis, the recognition that sexual behavior does not cease to be important in later life was the strongest predictor of holding a positive view on sexuality in later life. Greater knowledge is associated with more positive and permissive attitudes (Hillman & Stricker, 1996); therefore, if accurate facts are communicated, education may be the antidote to negative beliefs rooted in ageist stereotypes (Helmes & Chapman, 2012). This suggests if educators emphasized the importance and value of sexual expression for older adults across domains of health and well-being, it may be possible to dispel negative views of aging in later life.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have already shown that physical health, cardiovascular illnesses, diabetes and arthritis may influence the expression of sexuality (Helmes & Chapman, 2012;Lindau et al, 2007). …”
Section: Discussionmentioning
confidence: 99%